Isolation and Functional Analysis of PISTILLATA Homolog From Magnolia wufengensis - Liu, Wen; Shen, Xiangling; Liang, Hongwei; Wang, Yubing; He, Zhengquan; Zhang, Dechun; Chen, Faju (Frontiers in Plant Science, 2018)
PISTILLATA (PI) homologues are crucial regulators of flower development in angiosperms. In this study, we isolated the MAwuPI homologue from Magnolia wufengensis, a basal angiosperm belonging to the Magnoliaceae. Molecular phylogenetic analysis suggested that MAwuPI was grouped into the PI/GLO lineages of B-class MADS-box gene with the distinctive PI motif. Further expression profiling analysis showed that MAwuPI was expressed in tepals and stamens but not in juvenile leaves and carpels, similar to the spatial expression pattern of AtPI in Arabidopsis. Interestingly, MAwuPI had higher expression level in inner-tepals than in outer-tepals, whereas the M. wufengensis flower is homochlamydeous. Moreover, ectopic expression of MAwuPI in Arabidopsis pi-1 mutant emerged stamen-like structures but had no obvious petals, suggesting a partial phenotypic recovery of pi-1 mutant. The features of MAwuPI in the expression pattern and gene function improved our acknowledgement of B-class genes in M. wufengensis, and contributed to the clarification of M. wufengensis evolution status and relations with other sibling species in molecular perspective.